Evaluating respirable coal dust concentrations at the face of South African coal mines - Ferreira, Ernest French (My University, 2009)
Introduction The Department of Minerals and Energy (DME) in South Africa issued a Directive B7, titled “A Guideline for the Ventilating of Mechanical Miner Sections” to the coal mining industry. The main purpose of this directive was to reduce respirable dust exposures at the coal face with the long term objective of reducing the incidence of Coal Workers Pneumoconiosis (CWP). This study attempts to evaluate the appropriateness of the DME approach by comparing respirable coal dust results from personal samples from occupations at the coal face to the results obtained from engineering samples at the continuous miner. Objectives The objectives of this study are to: • Describe personal respirable coal dust concentrations of the occupations within the continuous miner Homogeneous Exposure Group (HEG) in five underground coal mines in Mpumalanga from January 2005 to December 2006. • Describe environmental engineering respirable coal dust concentrations of the continuous miner operator position in five underground coal mines in Mpumalanga from January 2005 to December 2006. • Compare personal respirable coal dust concentrations to Environmental Engineering Dust (EED) concentrations in five coal mines in Mpumalanga from January 2005 to December 2006. Methodology This study is descriptive in nature and was carried out utilizing historical respirable coal dust data from underground coal bord and pillar production sections. Data was supplied by Collieries Environmental Control Services (CECS) who provided a coal sampling and analysis service to South African collieries. Data provided was from five large underground coal mines in the Mpumalanga coal fields. The study population consisted of occupations within the HEG of workers deployed at the coal face who were linked to Continuous Miner (CM) production activities and results from EED sampling. Results When comparing the personal sampling results to EED sampling results for each individual mine, it is evident that all the mines had lower personal sampling results than EED results, thus establishing a definite trend. When combining all the mines in the two data sets it is also evident that EED sampling results are significantly higher than personal sampling results confirming the trend observed on individual mines. Correlation tests carried out between the two data sets indicated that there is no correlation between the personal and EED sampling results. The poor correlation between the two data sets indicates that the EED sampling position is not ideal and does not take account of the actual contaminant levels leaving the coal-winning heading. Discussion and conclusion The DME directive by way of a simple calculation took the countries personal Occupational Exposure Limit (OEL) of 2 mg/m3 and formulated a limit of 5 mg/m3 for EED sampling results. Simple extrapolation of the EED results indicates that personal exposure is exceeded more than two-fold and thus the limit of 5 mg/m3 as set by Directive B7 cannot be compared to the personal respirable coal dust OEL of 2 mg/m3. The basis of the initial calculation used to derive the 5 mg/m3 limit assumed that the shift lengths were in the region of 8 hours and cutting times around 40% of the shift, while most coal mines now have shift lengths ranging from 9 to 10 hours. In conclusion it is evident that the required limit of 5 mg/m3 as set out by Directive B7 cannot be related to the personal exposures limit of 2 mg/m3. Poor correlation results observed indicate that the EED sampling position does not account for the respirable dust concentrations leaving coal-winning headings and may be affected by the re-circulation of contaminated air over the sampling position. In addition the EED sampling position does not give an indication of the respirable dust capture efficiency of scrubber fans.
M.P.H., Faculty of Health Sciences, 2008
Keywords: respirable coal dust; coal mines; South Africa; evaluation